Report of 28th general assembly - ASEAN Inter-parliamentary organization - Asean Inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 2007)
Hội nghị lần thứ 28 của Tổ chức liên nghị viện ASEAN được tổ chức tại khách sạn Shangri-La, Kuala Lumpur, Malaysia từ ngày 19-24 tháng 8 năm 2007.